Investment process and the role of collective investments in the countries of Central and Eastern Europe - Shkut, Alexander P. (Journal of the Belarusian State University. Economics, 2023)
The article examines the investment process and the modern capital market in the countries of Central and Eastern Europe and their role in the economic development of these countries since 1990. Dependencies are established between the growth of fixed capital (production and infrastructure funds) and the growth of the economy and welfare. The strengths and weaknesses in the formation of the capital market of the Central and Eastern Europe countries and the role of collective investments in this are revealed.